A Method to Reduce Mechanical Injuries during Harvesting of Kinnow Fruits using a Vessel Filled with Water - Singh, Satya Vir (Journal of Agricultural Engineering, 2002)
Mechanical injuries during prevailing Kinnow harvesting practices contribute about 2-3% to the total losses. A vessel filled with water may be used for reducing mechanical injuries by taking advantage of buoyancy force of water on falling fruit. A mathematical analysis and field testing indicated that only 25 cm of water depth in the vessel would suffice for no fruit injury during decent in water under field conditions.